O inimigo em casa: os genocídios na Etiópia - Silva, Fernanda da (2023)
The present work questions: What are the causes of the genocides carried out by the Ethiopian ethnocratic regime (1974-1991)? To answer this question, the hypothesis was that, in ethnocracies, the exposure of minority ethnic groups with relevant mobilization potential to political and social segregation, while on a context of regional instability and crises of the state capacity, can lead to the execution of genocides by the State. Therefore, this study understood Ethiopia as a poliethnocracy and gave priority for two subcases: (1) the Ethiopian Red Terror (1977-79) and (2) the Famine (1983-85) and Forced Migration (1984-86). As result, the research found out that, despite consisting in a solid hypothesis to study ethnically motivated annihilation, the process tracing via qualitative method showed that the class social structure inside the ethnocracy s broader than the ethnic factor. This means that conflict may arise between ethnic groups (interethnic conflict) or between subgroups inside the same ethnic group (intraethnic conflict). Therefore, it is relevant to distinguish politicide and genocide when the object of study is an ethnocratic regime. This thesis also analyzed the mobilization of the Ethiopian Democratic Union (EDU), the Ethiopian People’s Revolutionary Party (EPRP), THE Pan-Ethiopian Socialist Movement (ME’ISON), the Eritrean People’s Liberation Front (EPLF) and the Tigrean People’s Liberation Front (TPLF). Thus, it was concluded that the existence of external alliances between an insurgent group and a foreigner State, be it direct or indirect, can change the magnitude of the genocidal or politicidal campaign. Therefore, the possibility of the ethnic group or political group targeted surviving the campaigns also raises. However, high dependance on external alliances reduces the insurgent group’s autonomy, generating a rebound effect as it undermines the group’s ability to stand up against the genocidal State. Previous alliances with the government can also result in the quick annihilation of the minority group. In the case of the State’s external alliances, the permissiveness of the allies, as well as the international community, is crucial for the execution of genocide and politicide. Furthermore, the EPLF example shows that even when there is no actual interest of the foreign actors to prevent or repress the crime of genocide, the interest of foreign States on the contested territory restrains the genocidal State. However, this does not prevent genocide, it only alters its magnitude and form. In any case, the thesis concludes that the combination of sociopolitical segregation, mobilizations potential, crisis of the state capacity and regional instability can act as causes of genocide. This happens because they pressure the elite, exposing the dominant ethnic group to the risk of power loss. All these conclusions were made using secondary sources and historic process tracing, as well as the hypothetico-deductive method. Also, the use of Laudanian metatheory allowed the use of multiple genocide theory traditions, which intersection built the theoretical base of this research. Among them, the government power, national crisis, and international traditions stand out when it comes to explaining the phenomena of genocide in Ethiopia.